Hydrogen-bond networks for proton couplings in G-Protein coupled receptors - Bondar, Ana-Nicoleta; Alfonso-Prieto, Mercedes (Frontiers in Physics, 2022)
G-protein signaling pathways mediate communication across cell membranes. The first steps of this communication occur at the cell membrane, where upon receiving an external signal –the binding of an agonist ligand- the membrane-embedded G- Protein Coupled Receptor adopts a conformation recognized by a cytoplasmatic G protein. Whereas specialized GPCRs sense protons from the extracellular milieu, thus acting as pH sensors in specialized cells, accumulating evidence suggests that pH sensitivity might be common to distinct GPCRs. In this perspective article we discuss general principles of protonation-coupled protein conformational dynamics and how these apply to GPCRs. To dissect molecular interactions that might govern the protonation-coupled conformational dynamics of GPCRs, we use graph-based algorithms to compute graphs of hydrogen bond networks. We find that the internal H-bond networks contain sites where structural rearrangements upon protonation change could be transmitted throughout the protein. Proton binding to bulk-exposed clusters of titratable protein sidechains ensures the pH sensing mechanism is robust.